Analysis of Eco-Theology Understanding of Islamic Boarding Schools in North Sumatra - Jamiluddin Marpaung (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This study aims to analyze the understanding and application of eco-theology in Islamic Boarding Schools in North Sumatra. Eco-theology connects religious teachings with human responsibility towards environmental stewardship, and in the Islamic context, it is based on the teachings of the Qur'an and hadith. The research used a qualitative method involving direct observation and in-depth interviews with Islamic Boarding Schools in the South Tapanuli region. The findings indicate that although Islamic Boarding Schools serve as pillars of religious education, the implementation of eco-theology concepts remains limited, particularly in terms of environmental management, such as river cleanliness and sanitation practices. The study concludes that there is a need to enhance environmental awareness in Islamic Boarding Schools through structured greening and waste management programs.